The condition of the working-class in England, 1209-2004 - Gregory Clark (University of California, Department of Economics, 2005)
The paper uses building workers' wages 1209-2004, and the skill premium, to consider the causes and consequences of the Industrial Revolution. Real wages were trendless before 1800, as would be predicted for the Malthusian era. Comparing wages with population, however, suggests 1640 actually was the break from the technological stagnation of the Malthusian era, long before the classic Industrial Revolution and even the arrival of modern democracy in 1689. Building wages also conflict with human capital interpretations of the Industrial Revolution, as modeled by Becker et al. (1990), Galor and Weil (2000) and Lucas (2002). Human capital accumulation began when the rewards for skills were unchanged, and when fertility was increasing.
Keywords: 330; Arbeiterklasse; Lohn; Bildungsertrag; Industrialisierung; England